Prospective study to determine the prevalence and contribution of maternal and fetal factors to neonatal thrombocytopenia - H R Nandish; Qudsiya Ansari; Poonam Wade (Indian Journal of Health Sciences and Biomedical Research KLEU, 2024)
BACKGROUND: Neonatal thrombocytopenia (platelet count <1.5 lakhs/μL) is one of the most common hematological findings in the neonates, admitted to the neonatal intensive care unit (NICU). The clinical features and laboratory parameters are heterogeneous, with different underlying causes and risk factors. There are still few studies about some possible risk factors and their influence on the newborn's clinical outcome. AIM: This study was conducted to assess the contribution of maternal and fetal factors, clinical profile, and outcome of neonatal thrombocytopenia in NICU. METHODS: A prospective observational study was conducted at our tertiary care hospital on 186 neonates with thrombocytopenia admitted to NICU. Maternal and neonatal risk factors were recorded. The risk factors were compared with the severity of thrombocytopenia. RESULTS: One hundred and eighty-six neonates with thrombocytopenia, based on platelet counts, were divided into three groups. Mild grade of thrombocytopenia was commonly seen (52.20%), followed by moderate (36.60%). Hypertension (HTN) was the most common maternal risk factor (24.70%), followed by eclampsia (15.10%) and gestational diabetes mellitus (GDM) (12.40%). The most common neonatal risk factors were birth asphyxia (37.60%), followed by intrauterine growth restriction (IUGR) (11.30%), sepsis (9.70%), and (11.80%), which had no risk factors. A significant association is found as all the 6 (3.3%) who died had severe thrombocytopenia. CONCLUSION: The most common maternal predisposing factors were HTN, eclampsia, and GDM. Birth asphyxia, IUGR, and sepsis were the most common neonatal factors associated with thrombocytopenia. Severe thrombocytopenia can be used as a prognostic indicator in sick neonates.